Microbiological quality assessment of selected ready-to-eat rice-based delicacies from Southern Leyte, Philippines. - Agero, Hazel Marie Laraga (2011.)
The microbial flora associated with the selected ready-to-eat rice-based delicacies namely budbud nilambiran, moron, and tres marias were assessed.
Thesis-B.S. (Food Technology) - School of Technology, University of the Philippines Visayas.
Keywords: Rice-based delicacies